2013
DOI: 10.1111/sms.12144
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of correlates of daily physical activity in Spanish children aged 8–9 years

Abstract: The aims of the study were (a) to examine the associations between the daily physical activity (PA) of 8- to 9-year-old children and their parents, and (b) to examine what effect the child's daily PA has on its cardiorespiratory fitness (CRF), body mass index (BMI), and health-related quality of life (HRQoL). The sample consisted of 1021 persons [351 children (8.73 ± 0.69 years in age) and 670 parents]. Pedometers were used to evaluate PA in parents and their children over the course of 4 days (Thursday-Sunday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…A partir de esta cuestión nos cabe destacar el efecto mediador del IMC entre variables predictoras, como ha sido el caso en estudios de los padres, edad y tiempo de pantalla, y la variable dependiente de actividad física. Los resultados obtenidos muestran que los niños activos, a diferencia de las niñas, presentan valores más bajos de IMC, aunque encontramos estudios que no hallan relación alguna entre IMC y actividad física (De Cocker et al, 2011;Saavedra, Escalante, Dominguez, Garcia-Hermoso, & Hernandez-Mocholi, 2013;Van Der Horst, Paw, Twisk, & Van Mechelen, 2007), o bien que los adolescentes con infrapeso tienden a ser más inactivos (Levin, Lowry, Brown, & Dietz, 2003).…”
Section: I E N C I Aunclassified
See 1 more Smart Citation
“…A partir de esta cuestión nos cabe destacar el efecto mediador del IMC entre variables predictoras, como ha sido el caso en estudios de los padres, edad y tiempo de pantalla, y la variable dependiente de actividad física. Los resultados obtenidos muestran que los niños activos, a diferencia de las niñas, presentan valores más bajos de IMC, aunque encontramos estudios que no hallan relación alguna entre IMC y actividad física (De Cocker et al, 2011;Saavedra, Escalante, Dominguez, Garcia-Hermoso, & Hernandez-Mocholi, 2013;Van Der Horst, Paw, Twisk, & Van Mechelen, 2007), o bien que los adolescentes con infrapeso tienden a ser más inactivos (Levin, Lowry, Brown, & Dietz, 2003).…”
Section: I E N C I Aunclassified
“…Aquellos progenitores con un estilo de vida activo se asocian con hijos/as más activos, como lo corroboran reciente estudios (Huang et al, 2013;Salazar, Feu, Vizuete, & de la Cruz-Sánchex, 2013;Wiley et al, 2011), aunque encontramos otros en los cuales la predicción viene determinada por el padre (Saavedra et al, 2013), o bien por la madre (Pahkala et al, 2007). Por otro lado, el nivel socioeconómico y su relación con la actividad física han sido ampliamente estudiados en adultos, pero mucho menos en niños y niñas.…”
Section: I E N C I Aunclassified
“…None Aerobic fitness: VERY LOW i 1 study reported no effect of PA intervention on aerobic fitness (Rowland et al 1996); 1 study reported a favourable effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on aerobic fitness between INT and CTRL, however, the intervention group decreased from baseline to post-test (Shore et al 2014) Muscular strength and endurance: 1 study reported a favourable effect of PA intervention on upper-body strength for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on muscular fitness; however, the control group improved upper body strength from baseline to post-test (Shore et al 2014) Flexibility: 1 study reported a favourable differential effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011) 1 study reported no differential effect of a PA intervention on flexibility, and an increase from baseline to post-test for the intervention group (Shore et al 2014 Butte et al 2007b;Hands et al 2009;Schofield et al 2009;Ruiz et al 2011;Machado-Rodrigues et al 2012;Martinez-Gomez et al 2012;Hjorth et al 2013;Lambourne et al 2013;Hansen et al 2014;Larouche et al 2014;Saavedra et al 2014) or mixed (favourable and null; 4/18 studies; Rizzo et al 2007;Dencker et al 2010;Kristensen et al 2010;Jimenez-Pavon et al 2013c) o VPA: associations were favourable (11/12 studies; Gutin et al 2005a;Ruiz et al 2006;Butte et al 2007b;Rizzo et al 2007;Lohman et al 2008;Martinez-Gomez et al 2010aKristensen et al 2010;Ottevaere et al 2011;Hay et al 2012;…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…Poitras et al n Includes 28 cross-sectional studies (Eiberg et al 2005;Gutin et al 2005a;Andersen et al 2006;Ruiz et al 2006Ruiz et al , 2011Butte et al 2007b;Rizzo et al 2007;Lohman et al 2008;Ortega et al 2008;Hands et al 2009;Schofield et al 2009;Dencker et al 2010;Kristensen et al 2010;Martinez-Gomez et al 2010a;Moliner-Urdiales et al 2010;Ottevaere et al 2011;Hay et al 2012;Machado-Rodrigues et al 2012;Hjorth et al 2013;Jimenez-Pavon et al 2013c;Lambourne et al 2013;Silva et al 2013;Larouche et al 2014;Hansen et al 2014;Santos et al 2014;Saavedra et al 2014;Aggio et al 2015) from 17 unique samples. Five studies reported data from the EYHS (Andersen et al 2006, Ruiz et al 2006Ortega et al 2008;Rizzo et al 2008;Kristensen et al 2010); 6 studies reported data from HELENA (Martinez-Gomez et al 2010a;Moliner-Urdiales et al 2010;Ottevaere et al 2011;Ruiz et al 2011;Martinez-Gomez et al 2012;Jimenez-Pavon et al 2013c); 2 studies reported data from the CoSCIS study (Eiberg et al 2005;Dencker et al 2010).…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…Several studies have examined the relationship between parents’ and their children’s objectively measured steps/day [1014], accelerometer-measured counts [9, 1517], light PA [18], and/or MVPA [9, 17, 19]. Most studies have reported a significant relationship with at least one parent, however many have also observed differences by parent or child gender.…”
Section: Introductionmentioning
confidence: 99%